HUBUNGAN ANTARA KELELAHAN KERJA DAN BEBAN KERJA DENGAN KINERJA PETUGAS PEMADAM KEBAKARAN DI SUDIN PEMADAM KEBAKARAN JAKARTA PUSAT TAHUN 2023 - Maryono (2023)
Performance was a crucial aspect of an organization's ability to achieve its goals. To enhance workers' performance, it was necessary to address the factors contributing to declining performance, such as work fatigue and workload. Decreased worker performance could increase the risk of workplace accidents. The aim of this study was to analyze the relationship between work fatigue and workload and the performance of firefighters. The research employed an observational analytical method with a cross-sectional study design. The study population consisted of 150 firefighters from the Sub of Department Central Jakarta Fire. The sampling technique utilized was simple random sampling, resulting in a sample size of 109 individuals calculated using the Slovin formula. Data analysis was conducted using the Chi-square test, and data were collected through a questionnaire. The research findings indicated a correlation between work fatigue (p = 0.005) and workload (p = 0.016) and the performance of firefighters in the Sub of Department Central Jakarta Fire. Therefore, it was recommended that the Central Jakarta Fire and Rescue Agency increase the number of personnel to reduce workload due to the shortage of staff. Regular monitoring and evaluation were also advised to gain better insights into the condition of the firefighters.